Back to the brink? Madagascar’s polarizing presidential elections - Resnick, Danielle (Brookings Institution, 2023)
Since the beginning of October, Madagascar’s capital city of Antananarivo, has been on edge. A massive military and police presence hovers along Independence Avenue in front of the mayor’s office to deter demonstrators from protesting the upcoming November 16 presidential elections. Despite the use of tear gas, batons, arrests, and widespread allegations of human rights abuses, the protesters have not been discouraged. Many are being mobilized to show different forms of resistance — on the streets and via social media — by the 10 opposition parties called the Collectif des candidats (group of candidates) who claim the incumbent president, Andry Rajoelina, is not qualified to run for a second term and that the electoral process cannot be trusted. While Rajoelina’s orange signs, featuring the party and face of the “Prezida” are plastered across the capital, most of the Collectif candidates have intentionally decided to pursue an electoral boycott. They insist that the upcoming elections be postponed and are taking the country to the threshold of civil conflict to achieve their goals.